2021
DOI: 10.1021/acssuschemeng.1c05597
|View full text |Cite
|
Sign up to set email alerts
|

Significantly Improved Energy Storage Performance of PVDF Ferroelectric Films by Blending PMMA and Filling PCBM

Abstract: The increasing energy problem and the demand of environmental protection raise higher requirements for the development of clean energy. Dielectric capacitors have attracted lots of attention as a supporting facility of energy storage and conversion for clean energy, but their further development is limited by the low energy storage performance. In this paper, all-organic composite dielectrics were reported, with a poly­(methyl methacrylate) (PMMA)/poly­(vinylidene fluoride) (PVDF) composite dielectric with dif… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
38
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 49 publications
(38 citation statements)
references
References 78 publications
0
38
0
Order By: Relevance
“…This minimized the structural defects introduced by the molecules and improved the composite dielectric’s polarization and breakdown strength synergistically. By doping 0.9 wt% PCBM, excellent energy storage properties (U e ~21.89 J/cm 3 ; η ~70.34%) were obtained under a 680 MV/m field intensity [ 131 ].…”
Section: Linear/nonlinear Polymer Dielectricsmentioning
confidence: 99%
“…This minimized the structural defects introduced by the molecules and improved the composite dielectric’s polarization and breakdown strength synergistically. By doping 0.9 wt% PCBM, excellent energy storage properties (U e ~21.89 J/cm 3 ; η ~70.34%) were obtained under a 680 MV/m field intensity [ 131 ].…”
Section: Linear/nonlinear Polymer Dielectricsmentioning
confidence: 99%
“…Small organic molecules have also been added to fluoropolymers to improve the energy storage performance. Rahimabady et al reported a surprisingly high breakdown strength (868 MV/m) in allorganic films composed of VDF oligomer and poly(vinylidene fluoride) (PVDF) [130] . A maximum polarization of 162 mC/m 2 is obtained since the coexistence of long and short PVDF chains facilitates the dense packing of rigid amorphous phase.…”
Section: All-organic Nanocompositesmentioning
confidence: 99%
“…The charge-discharge efficiency and discharged energy density of the PVDF-390 film are compared with those of pristine PVDF films in other recently published works [41][42][43][44][45][46][47][48][49][50][51][52][53][54][55][56] in Fig. 13, showing that the PVDF film irradiated with 390 kGy outperforms those other pristine PVDF films.…”
Section: Energy Storage Performancesmentioning
confidence: 99%